2017
DOI: 10.7555/jbr.31.20160059
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in arsenic trioxide encapsulated nanoparticles as drug delivery agents to solid cancers

Abstract: Since arsenic trioxide was first approved as the front line therapy for acute promyelocytic leukemia 25 years ago, its anti-cancer properties for various malignancies have been under intense investigation. However, the clinical successes of arsenic trioxide in treating hematological cancers have not been translated to solid cancers. This is due to arsenic's rapid clearance by the body's immune system before reaching the tumor site. Several attempts have henceforth been made to increase its bioavailability towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…8 However, it is difficult to achieve effective As 2 O 3 accumulation inside a solid tumor because of rapid clearance of this drug in blood circulation. 9,10 A high dose can be used to maintain the therapeutic activity but causes systemic adverse reactions. Many studies have aimed to determine how to maintain a therapeutic As 2 O 3 concentration within target solid tumor tissue for an extended period of time with few systemic adverse reactions has been the aim of the most studies.…”
Section: Introductionmentioning
confidence: 99%
“…8 However, it is difficult to achieve effective As 2 O 3 accumulation inside a solid tumor because of rapid clearance of this drug in blood circulation. 9,10 A high dose can be used to maintain the therapeutic activity but causes systemic adverse reactions. Many studies have aimed to determine how to maintain a therapeutic As 2 O 3 concentration within target solid tumor tissue for an extended period of time with few systemic adverse reactions has been the aim of the most studies.…”
Section: Introductionmentioning
confidence: 99%
“…This can also lead to deactivation of the drug as these organoarsenic drugs react readily with blood proteins, in particular transferrin [ 10 ]. In order to limit premature inactivation of the arsenic drugs, a range of nanoparticles have been developed to enhance stability, thus increase activity [ 11 12 ]. These nanoparticles have been decorated with targeting ligands to enhance the accumulation of the drug in cancer tissue.…”
Section: Introductionmentioning
confidence: 99%
“…However, two clinical trials showed synergistic treatment of TACE and ATO on HCC had better efficacy on preventing metastases and prolonging survival (Wang et al., 2015 ; Hu et al., 2017 ). The low solubility and quick elimination of ATO from blood stream are the main reasons that limit ATO to have adequate chemotherapeutic effect at the tumor site (Akhtar et al., 2017 ). On the other hand, people are reluctant to use high dose of ATO for prolonged period.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles and microspheres are effective tools for sustained drug delivery and multiple studies on ATO nanoparticles and microspheres have shown improved antitumor effects (Zhou et al., 2005 ; Yang et al., 2009 ; Zhou et al., 2012 ; Kalepu & Nekkanti, 2015 ; Akhtar et al., 2017 ; Ellison et al., 2017 ; Lu et al., 2018 ; Duan et al., 2019 ; Hu et al., 2019 ; Lian et al., 2019 ; Wu et al., 2020 ). The drug loading of ATO and its releasing pattern in these particles are essential for therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation